High Cure Rates for Hepatitis C Virus Genotype 6 in Advanced Liver Fibrosis With 12 Weeks Sofosbuvir and Daclatasvir: The Vietnam SEARCH Study. (9th June 2021) - Flower, Barnaby; McCabe, Leanne; Le Ngoc, Chau; Le Manh, Hung; Le Thanh, Phuong; Dang Trong, Thuan; Vo Thi, Thu; Vu Thi Kim, Hang; Nguyen Tat, Thanh; Phan Thi Hong, Dao; Nguyen Thi Chau, An; Dinh Thi, Tan; et al.
Abstract: Background: Genotype 6 is the most genetically diverse lineage of hepatitis C virus, and it predominates in Vietnam. It can be treated with sofosbuvir with daclatasvir (SOF/DCV), the least expensive treatment combination globally. In regional guidelines, longer treatment durations of SOF/DCV (24 weeks) are recommended for cirrhotic individuals, compared with other pangenotypic regimens (12 weeks), based on sparse data. Early on-treatment virological response may offer means of reducing length and cost of therapy in patients with liver fibrosis. Methods: In this prospective trial in Vietnam, genotype 6-infected adults with advanced liver fibrosis or compensated cirrhosis were treated with SOF/DCV. Day 14 viral load was used to guide duration of therapy: participants with viral load <500 IU/mL at day 14 were treated with 12 weeks of SOF/DCV and those ≥500 IU/mL received 24 weeks. Primary endpoint was sustained virological response (SVR). Results: Of 41 individuals with advanced fibrosis or compensated cirrhosis who commenced treatment, 51% had genotype 6a and 34% had 6e. The remainder had 6h, 6k, 6l, or 6o. One hundred percent had viral load <500 IU/mL by day 14, meaning that all received 12 weeks of SOF/DCV. One hundred percent achieved SVR12 despite a high frequency of putative NS5A inhibitor resistance-associated substitutions at baseline. Conclusions: Prescribing 12 weeks of SOF/DCV results in excellent cure rates in this population. These data support the removal of costly genotyping in countries where genotype 3 prevalence is <5%, in keeping with World Health Organization guidelines. NS5A resistance-associated mutations in isolation do not affect efficacy of SOF/DCV therapy. Wider evaluation of response-guided therapy is warranted. Abstract : Day 14 VL was used to determine whether HCV genotype 6-infected individuals with liver fibrosis should receive 12 or 24 weeks of sofosbuvir and daclatasvir. 100% had low viral load so all were treated for 12 weeks; 100% were cured.